ORGANOLEPTIC QUALITY BALI BEEF MARINED WITH PINEAPPLE SOLUTION (Ananas comosus) - N. M. T., Nainggolan; Sriyani, N. L. P.; Wibawa, A. A. P. P. (Jurnal Peternakan Tropika, 2023)
The purpose of this study was to determine the organoleptic quality of bali beef marinated with pineapple solution (Ananas comosus). The design used was a completely randomized design (CRD) with 4 treatments and 4 replications. The treatment given was marinating with distilled water (P0) as a control for 15 minutes. Marinate with pineapple fruit solution for 15 minutes, 30 minutes, and 45 minutes as P1, P2, and P3. The variables observed in this study were organoleptic tests, which included hedonic quality tests and hedonic tests (overall acceptance) of the parameters tested, including taste, color, aroma, texture, and tenderness. The results of this study indicate that the marinating of bali beef using a solution of pineapple (Ananas comosus) affects the organoleptic quality of bali beef and the most appropriate marinating time to produce organoleptic quality of meat is by soaking for 15 minutes. Keywords: bali beef, marinated, pineapple juice